Pengaruh faktor fundamental terhadap harga saham perusahaan pertambangan - ABDOEH, Moehammad ([Yogyakarta] : Universitas Gadjah Mada, 2010)
There are some factors that influence stock price changes. One of them is fundamental factors of the company. The fundamental factors describe internal condition of the company, which can be seen from financial statement. The purpose of this research is to know whether independent variables influence dependent variable (stock price) as a whole or partially, and how much the contributions of the independent variables to the dependent variable. The variables are taken from the conditions of mining companies. There are seven companies had been used as a sample in this research. Factors that analyzed are stock price as dependent variable, earning per share (EPS), debt to equity ratio (DER), book value (BV), price to book value (PBV), return on asset (ROA), and return on equity (ROE) as the independent varibles. From this research shows that all independent variables as a whole have significant influence to the stock price. As a partial only EPS, DER, and PBV that have significant influence to the stock price.